THE CONCEPT OF HAPPINESS AND ITS INTERPRETATION IN POEMS MUSA JALIL (Scientific journal of the Fergana State University, 2023)
The article reveals the motive of happiness in M. Jalil's lyrics as one of the main motives, and how this motive is changed by the author from stage to stage of his creative path, and how the motive in question "grows" together with the poet, deepens in content.